2016
DOI: 10.5604/17322693.1223796
|View full text |Cite
|
Sign up to set email alerts
|

Prothymosin-alpha and Ki-67 expression in pituitary adenomas

Abstract: The positive nuclear expression of Ki-67 and PTMA was observed in the majority of pituitary adenomas. Neither the expression of Ki-67 nor that of PTMA-c was related to tumor recurrence or local invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In addition, Ki67 is a dependable indicator of cancer cellular duplication and migration ( 62 ). Studies have suggested that in diverse cancers, Ki67 activation usually concurs with upregulated CYTOR, low expression of miR-206 or promoted PTMA ( 63 - 65 ), which is consistent with the results of the present study. Based on the above, the CYTOR/miR-206/PTMA axis may be valuable in NSCLC research.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Ki67 is a dependable indicator of cancer cellular duplication and migration ( 62 ). Studies have suggested that in diverse cancers, Ki67 activation usually concurs with upregulated CYTOR, low expression of miR-206 or promoted PTMA ( 63 - 65 ), which is consistent with the results of the present study. Based on the above, the CYTOR/miR-206/PTMA axis may be valuable in NSCLC research.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to sex chromosome-encoded genes, several autosomal genes were up-regulated in adenomas from male patients; of note, PDLIM2, PENK, SOX4, FH, PTMA and TMEM97 are all associated with tumourigenesis [64][65][66][67][68][69], and thus could play a role in the less favourable course of corticotrope adenomas in male patients. Links between these factors and the pituitary are known for PTMA and SOX4, as PTMA nuclear staining has been linked to pituitary tumour size [70], and SOX4 is involved in pituitary development, as shown in both zebrafish [71] and human tissues [72]. Along the same line, another gene overexpressed in male-derived adenomas associated with the pituitary is SPP1 (osteopontin) with increased expression reported in ACTH-secreting adenomas compared to non tumourous pituitary tissue [73] and in corticotrope and lactotrope adenomas compared to other pituitary tumours [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, association with age and female sex were found though there was no significant relationship with tumor regrowth [ 118 ]. However, other studies have found no relationship between PTTG expression and invasiveness in PitNETs [ 119 ] or nfPitNETs specifically [ 99 ].…”
Section: Biomarkersmentioning
confidence: 99%